-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.
Since there are two variables involved ... 'x' and 'y' ... a solution requires two equations. That's why the collection of equations is called a "system" of them. So far, in your question, you have supplied one equation. We eagerly await the arrival of the second one, so that we may begin working on the solution.
4x + 7 is an expression, not an equation. Only an equation (or an inequality) can have solutions, an expression cannot have a solution.
There is no solution yet, for x is an unknown. Once x is known, one can plug in the numbers. 4x-2=4x-2 because they are the exact same on both sides of the equal sign.
{-1,-2}
the solution for the inequality 4x + 2 - 6x < -1 was x < 3/2
If the equations are 8x + 7y = 37, and 2y = 4x -2 then the answer is yes.
All we have to do is subtract the coefficients of the x terms. The solution is -4x.
If you mean: y = x^2+4x+3 and y = 2x+6 Then the solution is: x = 1 or x = -3
4x-8-2 can be more easily written as 4x-10. The solution to this equation would be 5/2
-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.
Since there are two variables involved ... 'x' and 'y' ... a solution requires two equations. That's why the collection of equations is called a "system" of them. So far, in your question, you have supplied one equation. We eagerly await the arrival of the second one, so that we may begin working on the solution.
All we have to do is subtract the coefficients of the x terms. The solution is -4x.
It has no solution and if you mean 4x+10+3x+40-3x then it can be simplified to: 50+4x _________________________________________________________________________________________ Assuming that the equation is 4x+10+3x+40-3x = 0, then it will reduces to 4x = - 50, then the answer is: x = -12.5
4x+9=25 4x=16 x=4
Yes. It is THE solution.
4x + 7 is an expression, not an equation. Only an equation (or an inequality) can have solutions, an expression cannot have a solution.